2014
DOI: 10.5137/1019-5149.jtn.9452-13.0
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial spheno-ethmoidal sinus meningioma: case report

Abstract: Extracranial meningiomas of the paranasal sinus are the rare tumors of unclear etiology. We report a case of primary extracranial meningioma arising from the roof of the sphenoid sinus.A 60-year-old female presented with 5-month history of right visual disturbance. Imaging studies showed a mass in the sphenoid sinus extending into posterior ethmoid sinus. The tumor was resected completely including the affected bone of anterior cranial base via the endonasal endoscopic approach. Pathological diagnosis was meni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Only a few patients received radiotherapy (5.7%). The median duration of clinical follow-up was 12 months (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). We observed that PEMs have low recurrence (8.5%, n ¼ 5/59; Cases 13, 27, 49, 55, 57) with the median time from surgical resection to recurrence at 24 months (13-36).…”
Section: Treatment and Outcomesmentioning
confidence: 80%
See 1 more Smart Citation
“…Only a few patients received radiotherapy (5.7%). The median duration of clinical follow-up was 12 months (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). We observed that PEMs have low recurrence (8.5%, n ¼ 5/59; Cases 13, 27, 49, 55, 57) with the median time from surgical resection to recurrence at 24 months (13-36).…”
Section: Treatment and Outcomesmentioning
confidence: 80%
“…Majority were positive for S100 (68.8%, n ¼ 11), whereas none were positive for CD34 (n ¼ 0). All cases that tested for Ki-67 (n ¼ 9) were positive with varying labelling indexes ranging from 1 to 20%, [13][14][15][16][17][18][19][20][21] with majority of cases with labelling index of <5%.…”
Section: Radiological and Histopathological Findingsmentioning
confidence: 99%
“…Among all cases of meningiomas with extracranial localization involving the nasosinusal tract, the paranasal region has the tendency to be affected in more than one sinus [ 4 ]. The endoscopic endonasal approach represents the gold standard in the treatment of extracranial nasosinusal meningioma for its many benefits: direct and wide vision of the surgical field, multi-angled visualization, and scar-less surgery with minimal invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The endoscopic endonasal approach represents the gold standard in the treatment of extracranial nasosinusal meningioma for its many benefits: direct and wide vision of the surgical field, multi-angled visualization, and scar-less surgery with minimal invasiveness. In particular, considering the necessity to remove the attachments, a close-up visualization improves the macroscopic radicality [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation